Bibliometric Analysis of Deterministic Methods Used In Route Planning Problems - Şengül Coşkun (Journal of Business Administration and Social Studies)
The Vehicle Routing problem is an optimisation problem concerned with how to optimally distribute vehicles from a central depot to serve geographically distributed customers. In this study, the effectiveness of Deterministic Methods Used in Route Planning Problems in the context of Vehicle Routing Problem is investigated. The Vehicle Routing Problem is one of the most fundamental optimisation problems in logistics management and transportation, which aims to determine the optimal routes of vehicles serving geographically distributed customers from a given central warehouse. The aim of this study is to review the literature in this area using bibliometric analysis to evaluate the effectiveness of deterministic methods for solving Vehicle Routing problems and to identify current trends and future research directions. Bibliometric analysis clearly reveals gaps in the literature and future research opportunities as a method that provides a comprehensive review of the literature, identifying current research trends as well as potential future research directions. The results of the analysis show that deterministic methods are a powerful tool for finding optimal solutions in complex decision-making processes and that research in this field is gaining momentum. Furthermore, investigating the effectiveness of these methods in different application domains and comparing them with other optimisation techniques appear to be key areas for future research. The comprehensive information presented in this paper will help researchers and practitioners to understand Vehicle Routing problems and find effective ways to solve them.